Socio-Demographic Profile of An Integrated Counseling and Testing Centre Attendees: A Cross Sectional Study at A Tertiary Care Hospital in Gwalior, India - Mishra, Shraddha; Mishra, Ashok (National Journal of Community Medicine, 2013)
Background: Acquired immunodeficiency syndrome (AIDS) has emerged as one of the most serious public health problem in the country. Integrated counseling and testing centre’s (ICTCs) are key entry points for a wide range of interventions in HIV prevention and care. So this study was conducted to find out the socio-demographic profiles, HIV serostatus and risk behavior pattern of attendees and also elucidate the reasons for their visit to centre’s . Materials and Methods: The study was conducted among clients who visited ICTC either by self referral or referred by a health care provider from Oct. 2009 to Dec. 2009. It was a cross sectional, observational study and conducted at Integrated Counseling and Testing Centre attached to Microbiology department of G.R. Medical College, Gwalior. Results: Majority of attendees i.e. 83.2% of the attendees belonged to the age group of 15-45 years and males contributed to 64.75% of the case load in ICTC. An overall 7.06% of the ICTC attendees were HIV positive. The majority of the subjects were illiterate (35.65%). Illness was the main reason for ICTC visit of attendees. A high percentage of non response regarding the pattern of risk behavior was noted among the subjects (57.59% males and 88.37% females). Conclusion: In absence of curable drugs and vaccine, epidemiological studies should be carried out to find out behavioral, social and demographic factors which help in interruption and control of transmission of disease.